Constructing Long and Stable Ag‐Al2O3 Core–Shell Nanowires for Humidity Sensing and Triboelectric Energy Generation - Jiajun Fan; Tao Wan; Yilin He; Chao Liu; Tingting Mei; Yu‐Chieh Kuo; Ziheng Feng; Peiyuan Guan; Chun‐Ho Lin; Mengyao Li; Lin Fu; Mengdie Tao; et al. (Small Structures)
Silver nanowires (AgNWs) are a promising alternative material to indium tin oxide as flexible transparent electrodes owing to their excellent optoelectrical properties and mechanical performance. However, the main challenge is the poor stability under diverse environments, ranging from high humidity, chemical exposure, and dynamic mechanical deformation. Herein, ultralong AgNWs (≈100 μm) have been synthesized via controlling growth kinetics by a facile acetic acid‐assisted solvothermal method, further decorated with a thin Al2O3 layer by electrodeposition to form a core–shell architecture. The resultant films based on Ag‐Al2O3 core–shell nanowires (NWs) possess a higher conductivity while preserving the optical transparency due to the enhanced NWs contact. More importantly, the constructed films exhibit strong resistance to various conditions, such as exposure to high temperature/humidity and immersion in NaCl, HCl, and Na2S solutions. The laser‐etched interdigital electrodes based on the chemically stable AgNWs are further integrated with graphene oxide layer for humidity sensing and respiration monitoring. Furthermore, the developed NWs with superior mechanical stability are constructed as triboelectric nanogenerators for electricity generation, and reliable output performance has been demonstrated. This work provides a convenient, scalable, and cost‐effective solution that offers great potential for designing robust, transparent electrodes for next‐generation flexible electronics.